Multiple Perspectives on the Adoption of SMART Technologies for Improving Care of Older People: Mixed Methods Study - Elavsky, Steriani; Knapova, Lenka; Janiš, Kamil; Cimler, Richard; Kuhnova, Jitka; Cernicky, Tomas (JMIR. Journal of medical internet research, 2024)
BACKGROUND: Despite the ever-increasing offering of SMART technologies (ie, computer-controlled devices acting intelligently and capable of monitoring, analyzing or reporting), a wide gap exists between the development of new technological innovations and their adoption in everyday care for older adults. OBJECTIVE: This study aims to explore the barriers and concerns related to the adoption of SMART technologies among different groups of stakeholders. METHODS: Data from 4 sources were used: semistructured in-person or internet-based interviews with professional caregivers (n=12), structured email interviews with experts in the area of aging (n=9), a web-based survey of older adults (>55 years) attending the Virtual University of the Third Age (n=369), and a case study on the adoption of new technology by an older adult care facility. RESULTS: Although all stakeholders noted the potential of SMART technologies to improve older adult care, multiple barriers to their adoption were identified. Caregivers perceived older adults as disinterested or incompetent in using technology, reported preferring known strategies over new technologies, and noted own fears of using technology. Experts viewed technologies as essential but expressed concerns about cost, low digital competency of older adults, and lack of support or willingness to implement technologies in older adult care. Older adults reported few concerns overall, but among the mentioned concerns were lack of ability or interest, misuse of data, and limited usefulness (in specific subgroups or situations). In addition, older adults' ratings of the usefulness of different technologies correlated with their self-rating of digital competency (r=0.258; P<.001). CONCLUSIONS: Older adults appeared to have more positive views of various technologies than professional caregivers; however, their concerns varied by the type of technology. Lack of competence and lack of support were among the common themes, suggesting that educationally oriented programs for both older adults and their caregivers should be pursued.
Keywords: Aging; zlepšení kvality; elektronická pošta; strach; lidé; Quality Improvement; Fear; Electronic Mail; Technology; Humans; Aged; senioři; technologie; stárnutí